Anal carcinoma in HIV-infected patients in the period 1995–2009: A Danish nationwide cohort study. (June 2013) - Legarth, Rebecca; Helleberg, Marie; Kronborg, Gitte; Larsen, Carsten S.; Pedersen, Gitte; Pedersen, Court; Jensen, Janne; Nielsen, Lars Nørregård; Gerstoft, Jan; Obel, Niels
Abstract Background: Several studies have demonstrated an increased risk of non-AIDS cancers in HIV patients and, for some cancers, also in relatives of HIV patients. We aimed to estimate (1) the risk of anal carcinoma among HIV patients and their parents, and (2) the mortality after a diagnosis of anal carcinoma. Methods: We used Poisson regression to estimate the incidence rate ratios (IRR) of anal carcinoma in (1) a population of HIV patients identified from the Danish HIV Cohort Study (n = 4993) compared with a population control cohort matched on age and gender (n = 59, 916) for the period 1995–2009, and (2) parents of HIV patients compared with parents of controls for the period 1978–2009. Cancer diagnoses were identified from The Danish Cancer Registry. We further estimated the mortality rate ratios (MRR) of HIV patients compared with controls after the diagnosis of anal carcinoma. Results: Thirty-six HIV patients versus 8 population controls were diagnosed with anal carcinoma. HIV patients had an increased risk of anal carcinoma (IRR 77.9, 95% CI 36.2–167.7), especially among men who have sex with men (MSM) (IRR 101.4, 95% CI 39.3–261.5). Fathers of HIV patients had an increased risk of anal carcinoma (IRR 7.4, 95% CI 1.4–38.3) compared to fathers of population controls. Mortality after diagnosis of anal carcinoma was increased in male HIV patients compared with the male control cohort (MRR 3.2, 95% CI 1.1–9.2). Conclusions: Danish HIV patients, especially MSM, have a considerably increased risk of anal carcinoma. We cannot exclude that fathers of HIV patients have an increased risk of anal carcinoma.